2015
DOI: 10.1111/ajgw.12187
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for reducing alcohol concentration in wine

Abstract: Extending the time before harvest-and therefore increasing grape maturity-enhances ripe fruit wine flavours and wine colour intensity, and also decreases unripe green and vegetal wine flavours. Greater maturity, however, increases sugar concentration, which in turn leads to wines with elevated ethanol concentration. High ethanol concentration can reduce the complexity of a wine by suppressing aroma intensity, while also increasing the perception of 'hotness' and 'bitterness'. In addition, health and economic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 83 publications
2
102
0
1
Order By: Relevance
“…Multiple studies have shown that the concentration and composition of phenolics in wine can be positively related with the grade and market value of wine (Mercurio et al , Kassara and Kennedy ), and can in turn be influenced by both grape phenolics composition and the vinification process (Sacchi et al , Varela et al , Setford et al ). It was therefore pertinent to investigate the effect of varying harvest date on the extraction and retention of wine phenolics.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that the concentration and composition of phenolics in wine can be positively related with the grade and market value of wine (Mercurio et al , Kassara and Kennedy ), and can in turn be influenced by both grape phenolics composition and the vinification process (Sacchi et al , Varela et al , Setford et al ). It was therefore pertinent to investigate the effect of varying harvest date on the extraction and retention of wine phenolics.…”
Section: Resultsmentioning
confidence: 99%
“…This results in earlier harvest dates, 9 fast grape ripening, excessive sugar accumulation in berries, and resulting high-alcohol wines. 3,10,11,[12][13][14][15] Keller 16 shows that, in many cases, these phenomena have also been coupled to faster depletion of organic acids, high pH, and atypical green flavors in the grape because of the shortening ripening period and the shift towards the hotter part of the season.…”
Section: Introductionmentioning
confidence: 99%
“…Such wines are free from undesirable unripe, vegetable flavours but they also contain much higher levels of alcohol than wines made from early-harvested grapes. Depending on the particular style, too high a concentration of ethanol can be perceived as 'hotness' on the palate, making overly-alcoholic wines appear unbalanced [40][41][42].…”
Section: Striking the Right Chord Between Alcohol Strength And Fruitimentioning
confidence: 99%